Instructional Leadership and Role in Enhancing Teaching Quality in Islamic Schools - Nur Efendi (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2023)
This study investigates the role of instructional leadership in enhancing teaching quality at MAN 2 Tulungagung within an Islamic educational context. The study addresses how leadership shapes instructional practices, influences teaching quality, and connects leadership actions with learning outcomes. A qualitative case study design was employed to explore in-depth perspectives from the principal, teachers, and academic staff. Data were collected through semi-structured interviews, classroom observations, and document analysis, followed by thematic analysis. The findings indicate that instructional leadership strengthens teaching practices through structured supervision, constructive feedback, and sustained professional development. Teachers demonstrate improved instructional performance through organized lesson planning, interactive teaching strategies, and alignment with curriculum standards. Teaching quality is reflected in increased student engagement, effective classroom interaction, and consistent instructional delivery. The study also reveals an interconnected process in which leadership practices influence teacher performance, instructional practices shape learning experiences, and feedback informs leadership refinement. These results show that instructional leadership contributes significantly to sustaining teaching quality and supporting continuous improvement in Islamic school settings.